Relaciones comerciales con la Unión Europea en el Spaghetti-bowl de la Comunidad Andina de Naciones - Fairlie Reinoso, Alan (2007)
The article reflects on the roll that has the European Union like cohesion factor, considering that the relations are not limited the commercial plane in a context in which the Andean Community of Nations has had difficulties not only in its process of internal consolidation, but also to forge a common foreign policy. One discusses some differences with the FTA with the U.S.A., and the relations in these South-North agreements with regional integration. Of another side, one becomes a balance of the commerce flows, investment and cooperation between the EU and the Andean Community, being in evidence the fundamental importance that they have these bonds, beyond conjunctural losses of relative weight in the commercial aspect. There are limitations, but beyond the European restrictions or external these are fundamentally of internal character: insufficient exportable supply, competitiveness, infrastructure, etc.